Authority Control of Arabic Personal Names: RDA and Beyond. Issue 2 (13th April 2021) - Dagher, Iman; Soufi, Denise
Abstract: This paper discusses the basics of creating name authority records for Arabic personal names in accordance with Resource Description and Access instructions and Program for Cooperative Cataloging guidelines. A background into the use of romanization for non-Latin scripts in bibliographic and authority records is provided to establish the context. Issues with romanization that are particular to Arabic are addressed. Separate sections on modern and classical names provide an overview of the major challenges, and strategies to enhance discovery are outlined. The paper concludes with an examination of the possible benefits of identity management and other changes in the authority control landscape for names in non-Latin script.